S-Vivaldi:a space repairing based Internet delay space embedding algorithm - Zhan-feng WANG; Ming CHEN; Chang-you XING; Hua-li BAI; Xiang-lin WEI (Tongxin xuebao)
To counteract TIV’s influence on the Internet delay space models,an Internet delay space embedding algorithm based space repairing S-Vivaldi (scaling-Vivaldi) was proposed.S-Vivaldi firstly applied an exponent transformation on the delay matrix D,retrieved a matrix D'almost without TIV,and then embedded D'by the Vivaldi algorithm.The delay between any two nodes could be computed by a series of inverse transformation.Experimental results show that S-Vivaldi could improve the prediction accuracy apparently in the most case.